A brief online writing intervention improves positive body image in adults living with dermatological conditions - Adkins, Kate V.; Overton, Paul G.; Thompson, Andrew R. (Frontiers in Medicine, 2022)
Introduction Dermatological conditions can affect how individuals feel about their bodies. This research therefore seeks to evaluate the potential for a brief writing intervention, focused on body functionality, to improve body image in adults living with a range of dermatological conditions. Methods As part of a parallel Randomised Controlled Trial, 451 adults living with a dermatological condition were randomized to either three functionality-based writing tasks or three creative writing tasks (control). Of these, 155 participants completed pre- and post-intervention measures of body appreciation, functionality appreciation, appearance anxiety, skin-related shame, and skin-related quality-of-life. Results For participants with relatively low or mid-range scores on baseline body appreciation and functionality appreciation, there were medium-to-large positive effects of the intervention. Effects were smaller, with all but-one remaining significant, at 1-month follow up and in intention-to-treat analyses. No between-group effects of the intervention were found for measures of appearance anxiety, skin-related shame, and skin-related quality-of-life. Discussion These findings suggest that a 1-week writing intervention has the potential to improve positive aspects of body image, but not appearance- and skin-related distress in adults living with a dermatological condition. Clinical trial registration [https://clinicaltrials.gov/ct2/history/NCT044459 74?V_3=View], identifier [NCT04445974].